Molecular pathogenesis: Connections between viral hepatitis-induced and non-alcoholic steatohepatitis-induced hepatocellular carcinoma - Tian, Zelin; Xu, Chen; Yang, Peijun; Lin, Zhibin; Wu, Wenlong; Zhang, Wenjie; Ding, Jian; Ding, Rui; Zhang, Xuan; Dou, Kefeng (Frontiers in Immunology, 2022)
Hepatocellular carcinoma(HCC) is the sixth most common cancer in the world and is usually caused by viral hepatitis (HBV and HCV), alcoholic, and non-alcoholic fatty liver disease(NAFLD). Viral hepatitis accounts for 80% of HCC cases worldwide. In addition, With the increasing incidence of metabolic diseases, NAFLD is now the most common liver disease and a major risk factor for HCC in most developed countries. This review mainly described the specificity and similarity between the pathogenesis of viral hepatitis(HBV and HCV)-induced HCC and NAFLD-induced HCC. In general, viral hepatitis promotes HCC development mainly through specific encoded viral proteins. HBV can also exert its tumor-promoting mechanism by integrating into the host chromosome, while HCV cannot. Viral hepatitis-related HCC and NASH-related HCC differ in terms of genetic factors, and epigenetic modifications (DNA methylation, histone modifications, and microRNA effects). In addition, both of them can lead to HCC progression through abnormal lipid metabolism, persistent inflammatory response, immune and intestinal microbiome dysregulation.